2019
DOI: 10.1146/annurev-orgpsych-012218-015028
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Fit

Abstract: We review person-organization fit theory and research on selection and recruitment, and also highlight practical recommendations. The article is framed around explaining how and why people who are well matched to their organization experience optimal psychological reactions and performance. We address five key challenges to person-organization fit research and provide a brief overview of the critical distinction between “fitting in” decisions linked to the attraction-selection-attrition (ASA) model and day-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 90 publications
0
70
0
Order By: Relevance
“…Person-environment fit theory is one of the most compelling frameworks in the field of organizational psychology, and it serves as a critical conceptual foundation for understanding optimal behaviors at work [39,40]. In general, person-environment fit refers to "the degree of match between the values, norms, and other attributes held by both the person and the environment" ( [41], p. 172). Person-environment fit theory includes three main principles.…”
Section: Person-environment Fit Theory and Voluntary Green Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Person-environment fit theory is one of the most compelling frameworks in the field of organizational psychology, and it serves as a critical conceptual foundation for understanding optimal behaviors at work [39,40]. In general, person-environment fit refers to "the degree of match between the values, norms, and other attributes held by both the person and the environment" ( [41], p. 172). Person-environment fit theory includes three main principles.…”
Section: Person-environment Fit Theory and Voluntary Green Behaviormentioning
confidence: 99%
“…Existing research has suggested that employees who perceive fit with their organizations often feel belonged and committed [44,45]. Moreover, value congruence depicts a high relationship quality between employees and the organization, which allows employees to see themselves as insiders [41,46]. These inherent commonalities of employee-organization fit and perceived insider status suggest a positive association between them.…”
Section: The Mediating Role Of Perceived Insider Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…For an employee, complementary fit is high when the organization is able to consistently offer external resources that fill gaps in his or her existing repertoire of resources (Bundy et al, 2018). Barrick and Parks‐Leduc (2019) pinpointed that most employees have a strong need to achieve purposeful work goals which are broadly categorized as status, achievement, autonomy, and communion. The fulfillment of these employee needs by the organization is often evidenced via external manifestations.…”
Section: Reacting To Ceo Activismmentioning
confidence: 99%
“…Apart from the interview structure, the Person-Job (PJ) fit theory suggests that finding the match between the job candidate’s attributes and the job requirements is the cornerstone of a successful selection ( Barrick and Parks-Leduc, 2019 ). Hu et al (2016) show that supervisors’ Person-Organization fit perceptions are positively related to new hires’ performance for executives in a Fortune 500 company.…”
Section: Introductionmentioning
confidence: 99%